2018
DOI: 10.1007/s10534-018-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium complex: an appropriate candidate for killing hepatocellular carcinoma cancerous cells

Abstract: Hepatocellular carcinoma (HCC) is a prevalent human malignancy which its drug resistance is increasing world-wide. This project was designed to assess the anti-cancer effects of 4-bromo-2-(((5-chloro-2-hydroxyphenyl) imino) methyl) phenol ([IV(L)] complex) on the HepG2 cell line and also L929 cells, as normal cells. HepG2 and L929 cells were cultured in RPMI culture medium and the survival rates of the cells were determined after 24 and 48 h using MTT assay to find IC50 concentration of vanadium m, [IV(L)] com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…All experiments were done in triplicate. The cytotoxicity (%) was measured at different concentrations and the IC50 values were distinguished [15][16][17][18].…”
Section: Mtt Assaymentioning
confidence: 99%
“…All experiments were done in triplicate. The cytotoxicity (%) was measured at different concentrations and the IC50 values were distinguished [15][16][17][18].…”
Section: Mtt Assaymentioning
confidence: 99%
“…metal components, variations of the coordination mode, labile water molecules, and chelated ligands) probably exert an essential cooperative effect on the anti-tumor activity. Another in vitro study demonstrated that V as oxido-vanadium(IV) complex [VOL(bipy)] was able to induce early apoptosis more efficiently in the HepG2 cell line than in normal L929 cells [163]. Moreover, the authors revealed that the rates of necrosis/late apoptosis were also induced in the HepG2 cells more potently than in the L929 cells.…”
Section: Mechanisms Of the Anti-neoplastic Activity Of Vanadium: A Sumentioning
confidence: 99%
“…4 | DISCUSSION Some anticancer drugs are derived from natural resources such as herbal medicines 32 or bacteria. 33 However, the majority of these drugs were synthetized chemically from different compounds and were used as chemotherapeutic agents for treatment of different cancers for example vanadium 34 and Cu 35 complexes, indole derivatives, 36,37 proline-derived compounds, 38 and so forth. But because of the change in the nature of cancer cells and their escape from death and resistance to anticancer drugs, research to find new compounds with new anticancer properties has always been one of the major concerns of researchers.…”
Section: F I G U R Ementioning
confidence: 99%